Pelaksanaan Supervisi Pendidikan Dalam Rangka Meningkatkan Kualitas Pesantren di Pondok Pesantren Tahfidz Qur’an Harun Asy-Syafi’i - Indriana Pitaloka; Undang Ruslan Wahyudin (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2022)
This article discusses the implementation of educational supervision in order to improve the quality of pesantren in the Islamic Boarding School Tahfidz Qur'an Harun Asy-Shafi'i. This study uses a type of qualitative research and case studies as a form of in -depth research. The results showed that in the implementation of supervision activities carried out by the principal with an open meeting all teachers were given the opportunity to issue opinions about learning achievement, and problems faced by the teacher. Conduct class visits to find out the situation and atmosphere of the learning and evaluation process as a whole. The implementation of this supervision is said to be successful if the achievement of the target of the cottage has been achieved.